1979
DOI: 10.1002/cpt1979265660
|View full text |Cite
|
Sign up to set email alerts
|

Effects of allopurinol on theophylline metabolism and clearance

Abstract: The effects of allopurinol on the plasma clearance and metabolism of theophylline in man were investigated under single-dose and multiple-dosing conditions. No change in theophylline clearance was found with the concomitant use of allopurinol but 1-methylxanthine (1MX), a theophylline metabolite not previously described in man, was detected in urine during control and allopurinol treatment phases under both single- and multiple-dosing conditions. 1MX excretion increased at the expense of 1-methyluric acid (1MU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
0

Year Published

1981
1981
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(42 citation statements)
references
References 4 publications
5
37
0
Order By: Relevance
“…We looked for 1-MX in our samples and could find no evidence of its presence. Grygiel et al (1979) did find what appeared to be about 1% of the total dose of theophylline recovered in the urine as 1-MX and this fraction rose dramatically when the xanthine oxidase inhibitor allopurinol was administered. Unfortunately, the subjects were on a xanthine-restricted diet for only 24 h prior to the study.…”
Section: Discussionmentioning
confidence: 97%
“…We looked for 1-MX in our samples and could find no evidence of its presence. Grygiel et al (1979) did find what appeared to be about 1% of the total dose of theophylline recovered in the urine as 1-MX and this fraction rose dramatically when the xanthine oxidase inhibitor allopurinol was administered. Unfortunately, the subjects were on a xanthine-restricted diet for only 24 h prior to the study.…”
Section: Discussionmentioning
confidence: 97%
“…Theophylline (1,3-dimethylxanthine) is extens- & Miech, 1976;Grygiel et al, 1979;Jonkman et ively metabolised by hepatic cytochrome P-450 al., 1981;Tang-Liu et al, 1982;Birkett et al, dependent enzymes. Only about 10% of a theo-1985). phylline dose is excreted unchanged in urine.…”
Section: Introductionmentioning
confidence: 99%
“…It must be given by the intravenous route as it is poorly absorbed orally, and its approval for human use requires extensive documentation for each batch. To overcome these problems, the present study investigated the use of 1MX derived as an intermediary metabolite of theophylline (Birkett et al, 1983;Grygiel et al, 1979) to assess the degree of xanthine oxidase inhibition during allopurinol therapy. Our previous study (Day et al, 1988a) showed that the relationship between plasma oxipurinol concentration and 1MU/1MX ratio was the same at steady state and during oxipurinol washout.…”
Section: Introductionmentioning
confidence: 99%